Metoda reducerii
{4a-3b+7=0
{ b=a+3
Răspunsuri la întrebare
Răspuns de
1
salut!
4a-3•(a+3)+7=0
4a-3a+7=0
a+7=0
a=0-7
a=-7
b=-7+3
b=-4
4a-3•(a+3)+7=0
4a-3a+7=0
a+7=0
a=0-7
a=-7
b=-7+3
b=-4
cristiannicolae2:
Thx
Răspuns de
0
Răspuns:
{4a-3(a+3)+7=0=>4a-3a-9+7=0=>a-2=0=>a=2(am inlocuit cu relația dată (b=a+3)
{b=a+3=>b=2+3=5
=>{a=2
{b=5
Alte întrebări interesante
Franceza,
8 ani în urmă
Geografie,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
8 ani în urmă
Biologie,
8 ani în urmă
Limba română,
9 ani în urmă